Culture incorporated : museums, artists, and corporate sponsorships - Rectanus, Mark W. (University of Minnesota Press, 2002)
In Culture Incorporated, Mark W. Rectanus calls for full disclosure of corporate involvement in cultural events and examines how corporations, art institutions, and foundations are reshaping the cultural terrain. In turn, he also shows how that ground is destabilized by artists subverting these same institutions to create a heightened awareness of critical alternatives.